1058. Demographics of Hepatitis C Virus Antibody and RNA Positivity within an Emergency Department Screening Program. (31st December 2020) - Segal, Talia A; Ata, Ashar; Rowden, Adam; Wales, Danielle P; Waxman, Michael
Abstract: Background: In support of the recent United States Preventive Services Task Force's (USPSTF) revised recommendations for non-targeted HCV screening, we have noted a shift away from active infections within the birth cohort (patients born between 1945-1965), as these individuals have often undergone successful treatment, and a shift towards younger adults who are RNA positive, especially people who use intravenous drugs (PWID). Methods: Located in Northeastern New York State, Albany Medical Center conducts routine emergency department (ED) HCV screening, with active linkage to care. We performed a retrospective study of our HCV linkage to care data from April 2019 to June 2020. Patients were offered screening if they belonged to the birth cohort, were PWID, or at staff discretion. We estimated the effect of birth cohort, intravenous drug use and other potential risk factors on RNA positivity via Chi-square tests and Modified Poisson Regression. Results: There were 242 people that were HCV antibody positive. The mean age was 50.9 years-old, with 118 (46.8%) in the birth cohort and 103 (42.56%) PWID. As compared to the birth cohort, a significantly greater proportion of non-birth cohort patients were PWID (62% vs 21.2%, p< 0.01) and homeless (17.7% vs 9.3%, p=0.05). Birth cohort patients were 0.55 times (95%CI: 0.39 to 0.79) less likely to be RNA positive. PWID were 2.22 times (95% CI: 1.58 to 3.13) and homeless people were 2.05 times (95% CI: 1.50 to 2.80) more likely to be RNA positive. After multivariable adjustment, birth cohort was not a significant risk factor for RNA positivity but PWID (RR: 1.84; 95% CI: 1.26 to 2.68) and homelessness (RR: 1.69; 95% CI: 1.20 to 2.39) were significantly associated with RNA positivity. Conclusion: These data suggest that the RNA positivity rate is higher among the non-birth cohort age group but is explained by the higher prevalence of drug use and homeless. The findings support USPSTF's new guidelines for testing all adults and shed light on the demographics of populations at risk for active infection vs. populations who are antibody positive and RNA negative. Further research might explore (a) whether these findings are applicable to other clinical settings and geographic locations and (b) the feasibility of targeting patients with active infection in settings such as the ED. Disclosures: Talia A. Segal, BS, GILEAD FOCUS Foundation (Grant/Research Support) Ashar Ata, MD, MPH, PHD, GILEAD FOCUS Foundation (Grant/Research Support) Adam Rowden, DO, GILEAD FOCUS Foundation (Grant/Research Support) Danielle P. Wales, MD, MPH, Gilead (Grant/Research Support) Michael Waxman, MD, MPH, Gilead FOCUS Foundation (Grant/Research Support)